An acidic cadmium-arsenic composite pollution synergistic passivation soil modifier, and a preparation method and application thereof
Patent Information
- Application Number
- CN202611220335.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]本发明的目的在于提供一种酸性镉砷复合污染协同钝化土壤改良剂及其制备方法与应用,具体是以腐植酸改性镁铁水滑石、氨基酸功能化复合水热炭、硅藻矿粉、黄磷渣粉为原料,采用两段式纯固相球磨法进行制备M-H-LDHs及原料复配,所得改良剂能通过不同反应路径协同钝化Cd和As,有效解决了现有原位钝化材料在处理酸性农田镉砷复合污染时常出现的“钝化一种、活化另一种”的问题
[0053]1、原始镁铁水滑石主要依赖带正电层板、层间阴离子交换和金属羟基位点;本发明通过腐植酸改性后,一方面引入羧基、酚羟基等软硬配位位点,增强对Cd等阳离子的络合,另一方面球磨引起的颗粒细化、层板堆叠无序化和表面羟基暴露提高界面反应可达性;腐植酸还可通过有机质-Fe桥联影响As结合。同时,本发明通过球磨法进行高能机械活化,将腐植酸分子牢固插层进入水滑石层间并附着于表面,避免了游离状态的腐植酸与污染物形成可溶络合物,进一步提升镉砷共钝化效果。SEM对比结果表明,机械化学改性使原始镁铁水滑石的大尺寸致密团聚结构发生破碎和解聚,增加了颗粒边缘、断裂面及颗粒间隙,有利于提高反应位点的可达性以及材料在复合体系中的分散性。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of farmland soil heavy metal pollution remediation technology, specifically involving an acidic cadmium and arsenic compound pollution synergistic passivation soil conditioner and its preparation method, as well as its application in farmland soil in-situ passivation remediation and crop safety production assurance. Background Technology
[0002] Soil, as the foundation of agricultural production, is crucial for maintaining global food supply. However, with the rapid advancement of industrialization and agricultural intensification, activities such as mining, smelting, coal combustion, and the irrational application of agricultural chemicals have led to the entry of large amounts of heavy metals into farmland ecosystems. Among them, cadmium (Cd) and arsenic (As) are classified as Group 1 carcinogens by the International Agency for Research on Cancer (IARC) of the World Health Organization due to their high toxicity, high mobility, long persistence, and ease of accumulation by plants. Furthermore, Cd and As exhibit some spatial overlap, demonstrating characteristics of compound pollution. Particularly in the red soil regions of southern China, where soils are generally acidic, acidic conditions not only significantly enhance the leaching and migration of Cd but also profoundly affect the chemical transformation and surface adsorption behavior of As, further exacerbating the ecological risks of Cd-As compound pollution. Therefore, to achieve sustainable development goals, the remediation of Cd-As compound pollution in farmland soils, especially the synergistic control of Cd-As compound pollution under acidic conditions, has become a critical issue urgently needing to be addressed to ensure my country's food security.
[0003] Currently, remediation methods for heavy metal pollution in soil mainly include in-situ passivation, phytoremediation, electrodynamics, and topsoil replacement. Farmland soil remediation generally follows the principle of "remediation while production continues." Therefore, in-situ passivation technology, with its advantages of low remediation cost, simple operation, rapid results, and suitability for large-scale promotion, has significant advantages. However, traditional in-situ passivation materials (such as lime, phosphates, biochar, and clay minerals) can usually only effectively passivate one element, and during application, they can easily activate and release another element, making it difficult to meet the remediation needs of soils with complex pollution.
[0004] Especially for soils contaminated with Cd-As complexes, Cd mainly exists in the form of cations (Cd... 2+ As exists primarily in the form of oxyanions (such as H₂AsO₄), whose activity and mobility decrease with increasing pH. As can be fixed by increasing soil pH or by forming carbonate / phosphate precipitates. - ,HAsO4 2-The adsorption and fixation of Cd or As rely on specific adsorption sites on the surfaces of iron and aluminum oxides, and they are easily activated and released due to electrostatic repulsion under excessively high pH conditions. Conventional passivation materials can only adjust specific pH or provide specific adsorption sites to fix Cd or As heavy metals, but they inevitably disrupt the original chemical balance of the soil, leading to the activation of another heavy metal. In addition, the acidic soils in southern my country have low pH, high proportion of variable positive charge, and low cation exchange capacity, which further increases the technical difficulty of synergistic passivation.
[0005] In summary, developing a soil conditioner that can efficiently passivate both cationic Cd and anionic As in complex acidic soil environments is crucial and a problem that urgently needs to be solved by those skilled in the art.
[0006] In view of the above, this invention is hereby presented. Summary of the Invention
[0007] The purpose of this invention is to provide a soil conditioner for synergistic passivation of acidic cadmium and arsenic compound pollution, its preparation method, and its application. Specifically, it uses humic acid-modified magnesium-iron hydrotalcite, amino acid-functionalized composite hydrothermal carbon, diatomaceous earth powder, and yellow phosphorus slag powder as raw materials. MH-LDHs and raw material compounding are prepared using a two-stage pure solid-phase ball milling method. The resulting conditioner can synergistically passivate Cd and As through different reaction pathways, effectively solving the problem of "passivating one while activating another" that often occurs with existing in-situ passivation materials when treating acidic farmland cadmium and arsenic compound pollution.
[0008] Applying the prepared soil conditioner to contaminated soil effectively improves the acidic microenvironment, significantly reduces the available cadmium and arsenic content in the soil, greatly alleviates heavy metal toxicity stress, and inhibits the migration and accumulation of cadmium and arsenic into crop tissues, thereby promoting healthy crop growth. The soil conditioner provided by this invention requires a small application rate, has significant soil remediation effects, and can greatly increase agricultural yields.
[0009] The first aspect of the present invention is to provide a soil conditioner for synergistic passivation of acidic cadmium and arsenic compound pollution, comprising the following components by weight: 30-50 parts of humic acid modified hydrotalcite, 20-40 parts of amino acid functionalized composite hydrothermal carbon, 10-30 parts of diatomite powder, and 5-20 parts of yellow phosphorus slag powder.
[0010] In a preferred embodiment, the total weight of the humic acid-modified hydrotalcite, amino acid-functionalized composite hydrothermal carbon, diatomaceous earth powder, and yellow phosphorus slag powder is 100 parts.
[0011] In a preferred embodiment, the total weight of the humic acid-modified hydrotalcite and amino acid-functionalized composite hydrothermal char is 70 parts, serving as the core chemical active phase; the total weight of the diatomaceous earth powder and yellow phosphorus slag powder is 30 parts, serving as the auxiliary dispersion / buffer phase; preferably, the acidic cadmium-arsenic composite pollution synergistic passivation soil conditioner, by weight, comprises the following components: 40 parts of humic acid-modified hydrotalcite, 30 parts of amino acid-functionalized composite hydrothermal char, 20 parts of diatomaceous earth powder, and 10 parts of yellow phosphorus slag powder.
[0012] In a preferred embodiment, the method for preparing the humic acid-modified hydrotalcite includes the following steps:
[0013] (1) Dissolve soluble magnesium salt and soluble iron salt in deionized water to prepare a mixed metal salt solution, then mix it with alkaline solution, react it by nucleation crystallization isolation method, and age it by constant temperature stirring to obtain the original magnesium iron hydrotalcite powder.
[0014] (2) Mix the original magnesium-iron hydrotalcite powder with humic acid. The resulting mixture is then subjected to high-energy mechanical activation by ball milling, so that the humic acid molecules are firmly intercalated into the hydrotalcite interlayer and attached to the surface, thus obtaining humic acid modified hydrotalcite, denoted as MH-LDHs.
[0015] Preferably, in step (1), the soluble magnesium salt is MgCl2·6H2O, and the soluble iron salt is FeCl3;
[0016] Preferably, in step (1), Mg in the mixed metal salt solution 2+ with Fe 3+ The molar ratio is (1~3):1, and the total metal ion concentration is 0.1~0.6 mol / L; more preferably, in the mixed metal salt solution, Mg 2+ with Fe 3+ The molar ratio is 2:1, and the total metal ion concentration is 0.6 mol / L;
[0017] Preferably, in step (1), the alkaline solution is an aqueous solution of sodium hydroxide, the concentration of sodium hydroxide in the alkaline solution is 0.1~0.2 mol / L, and the molar amount of sodium hydroxide in the alkaline solution is equal to the amount of Mg in the mixed metal salt solution. 2+ with Fe 3+ The total molar amount is 1.8 to 2.5 times; more preferably, the concentration of the alkaline solution is 0.15 mol / L, and the molar amount of sodium hydroxide in the alkaline solution is equal to the molar amount of Mg in the mixed metal salt solution. 2+ with Fe 3+ Twice the total molar amount;
[0018] Preferably, in step (1), the specific operation of the nucleation crystallization isolation method includes: simultaneously adding the mixed metal salt solution and the alkaline solution into the colloid mill, and carrying out the nucleation reaction by high-speed shearing; more preferably, the high-speed shearing speed is 3000~5000 r / min, and the shearing time is 1~5 min;
[0019] Preferably, in step (1), the constant temperature is 75~85℃ and the stirring aging time is 3~5 h; more preferably, the stirring aging speed is 800~1200 r / min.
[0020] Preferably, in step (1), after the constant temperature stirring and aging, the process further includes conventional solid-liquid separation, washing, drying, grinding and sieving steps; wherein, the washing method includes: washing with deionized water until the washing liquid is neutral; the drying can be carried out using conventional methods known to those skilled in the art, such as drying at 40~60℃ for 2~8 h; the sieving mesh size is 100 mesh;
[0021] Preferably, in step (2), the mass ratio of the original magnesium-iron hydrotalcite powder to humic acid is (8~12):1; more preferably, the mass ratio of the original magnesium-iron hydrotalcite powder to humic acid is 10:1.
[0022] Preferably, in step (2), the humic acid has a molecular weight of 321 kDa and a content of over 90%;
[0023] Preferably, in step (2), the process parameters of the ball milling method include: using a planetary ball mill, using zirconia balls, having a ball diameter of 3~8 mm, a ball-to-material mass ratio of (4~8):1, a revolution speed of 200~500 r / min, and a total ball milling time of 7.5~12.5 h;
[0024] Preferably, in step (2), the specific operation of the high-energy mechanical activation includes: clockwise ball milling for 1 hour, pausing for 0.5 hours, and counterclockwise ball milling for 1 hour as a cycle, and repeating the cycle 3 to 5 times.
[0025] Preferably, in step (2), the X-ray diffraction (XRD) pattern of the humic acid-modified hydrotalcite obtained shows obvious (003), (006), and (009) crystal plane characteristic diffraction peaks at 2θ angles of approximately 11.21°, 22.60°, and 33.91°, respectively, reflecting its good layered structure.
[0026] Preferably, in step (2), the humic acid-modified hydrotalcite prepared has an average pore size of 20.9768 nm and a pore volume of 0.038320 cm³. 3 g −1 Its specific surface area is 6.6377 m². 2 g−1 .
[0027] In this invention, humic acid-modified hydrotalcite is used as the core active phase for cadmium-arsenic co-passivation. The magnesium-iron hydrotalcite possesses positively charged lamellar plates, exchangeable interlayer anions, and Mg / Fe-OH surface sites. Arsenic is fixed through anion exchange, electrostatic adsorption, and Fe-O-As internal coordination complexation, while cadmium activity is reduced through surface complexation, ion exchange, and local alkalization-induced precipitation. The humic acid functionalization in this invention adds oxygen-containing coordination groups such as carboxyl and phenolic hydroxyl groups to the material surface, further enabling Cd complexation. 2+ Meanwhile, ball milling further breaks down the particles, disrupts the crystal layers, and exposes surface hydroxyl groups, thus improving the accessibility of active sites. Compared to unfunctionalized LDH, the humic acid-modified hydrotalcite designed in this invention forms a composite interface of inorganic laminar anion binding sites and organic oxygen-containing cationic binding sites, making it more suitable for addressing the significant differences in the main forms of Cd and As in soil, their interfacial reaction mechanisms, and their responses to pH and redox conditions. It should be noted that the inventors, through extensive research, discovered that humic acid can both promote adsorption and form soluble complexes with pollutants in its free state. Therefore, this invention employs a mechanochemical loading method to immobilize humic acid at the LDH interface as much as possible, rather than directly adding free humic acid to the soil.
[0028] In a preferred embodiment, the preparation method of the amino acid functionalized composite hydrothermal char includes the following steps: mixing cotton stalk powder and lignite powder as a solid precursor, adding diluted amino acid mother liquor, and conducting a co-hydrothermal reaction in a closed reactor at a temperature of 200~240°C to obtain amino acid functionalized composite hydrothermal char, denoted as HTC.
[0029] Preferably, the method for preparing the cotton stalk powder includes: rinsing the waste cotton stalks with deionized water, drying them at 60-80°C to constant weight, crushing them and passing them through a 100-mesh sieve;
[0030] Preferably, the preparation method of the lignite powder includes: taking natural lignite, crushing and grinding it, and passing it through a 100-mesh sieve;
[0031] Preferably, the mass ratio of cotton stalk powder to lignite powder is 1:(0.8~1.2); more preferably, the mass ratio of cotton stalk powder to lignite powder is 1:1.
[0032] Preferably, the diluted amino acid mother liquor is obtained by diluting amino acid mother liquor with deionized water at a volume ratio of 1:(30~70), and the main components of the amino acid mother liquor include 50~90 g / L of free amino acids, 100~200 g / L of organic matter, and a pH of 4~6; more preferably, the amino acid mother liquor is diluted with deionized water at a volume ratio of 1:50.
[0033] Preferably, the solid-liquid ratio of the solid precursor to the diluted amino acid mother liquor is 1 g: (8~12) mL; more preferably, the solid-liquid ratio of the solid precursor to the diluted amino acid mother liquor is 1 g: 10 mL.
[0034] Preferably, the heating rate is 3~7℃ / min; more preferably, the heating rate is 5℃ / min.
[0035] Preferably, the hydrothermal reaction time is 1-3 hours;
[0036] Preferably, after the hydrothermal reaction, the process further includes conventional solid-liquid separation, washing, drying, grinding, and sieving steps; wherein, the washing method includes: washing with deionized water until the washing liquid is neutral; the drying can be carried out using conventional methods known to those skilled in the art, such as drying at 70~90℃ for 6~18 h to constant weight; the sieve mesh size is 100 mesh;
[0037] Preferably, the prepared amino acid functionalized composite hydrothermal carbon has a carbon (C) content of 44.22%, a hydrogen (H) content of 4.62%, a nitrogen (N) content of 2.26%, a sulfur (S) content of 0.77%, and an oxygen (O) content of 25.87%.
[0038] In this invention, the amino acid-functionalized composite hydrothermal char primarily functions as a Cd binder, carrier support, and organic carbon skeleton. Cotton stalks, after hydrothermal carbonization, retain a certain number of oxygen-containing functional groups such as carboxyl and hydroxyl groups, while lignite provides an aromatic carbon skeleton and a humic-like structure. During the hydrothermal process, the amino acid mother liquor undergoes dehydration, condensation reactions, and partial nitrogen-containing structure immobilization, increasing the number of amino / amide nitrogen-containing sites in the resulting hydrothermal char. Amino and carboxyl groups can bind Cd through coordination or electrostatic interactions. 2+ The porous carbon framework can also support and disperse humic acid-modified magnesium-iron hydrotalcite, diatomaceous earth powder, and yellow phosphorus slag powder components, reducing mineral particle agglomeration and improving the mass transfer efficiency of pollutants to active sites. It should be noted that in this invention, the amino acid-functionalized composite hydrothermal carbon not only serves as the sole main active phase for arsenic fixation but also, in combination with Fe-rich humic acid-modified magnesium-iron hydrotalcite and calcium silicate minerals, solves the problem of insufficient As fixation capacity of individual carbon materials.
[0039] In a preferred embodiment, the diatomaceous earth powder and / or yellow phosphorus slag powder, after drying and sieving, have a particle size of less than 100 mesh.
[0040] In this invention, diatomaceous earth powder mainly serves as a porous silica carrier, a dispersed phase, and a soil physical conditioning phase. Its pore structure and surface silanol groups provide certain physical adsorption and surface binding sites, and isolate humic acid-modified magnesium-iron hydrotalcite, amino acid-functionalized composite hydrothermal carbon, and yellow phosphorus slag powder during low-energy ball milling, preventing material agglomeration and promoting a more uniform distribution of different active phases in the soil; at the same time, it can improve the material's fluidity, water retention, and soil pore structure.
[0041] In this invention, yellow phosphorus slag powder serves as a buffer against acidic soil conditions and a reactant phase for calcium-silica minerals. Typical yellow phosphorus slag is primarily composed of a CaO-SiO2 glassy phase and a dicalcium silicate-like phase, which can gradually consume H+ in an acidic environment. + It releases Ca / Si and enhances the adsorption capacity of Cd on the surface of variable-charge minerals; increasing pH can also promote the transformation of Cd from the exchange state to the carbonate-bound state, hydroxide or silicate-bound state.
[0042] A second aspect of the present invention provides a method for preparing a soil conditioner for synergistic passivation of acidic cadmium and arsenic compound pollution, comprising the following steps:
[0043] S1 prepared humic acid-modified hydrotalcite and amino acid-functionalized composite hydrothermal carbon for later use; diatomaceous earth powder and yellow phosphorus slag powder were dried to constant weight and sieved for later use.
[0044] S2. The humic acid-modified hydrotalcite, amino acid-functionalized composite hydrothermal carbon, diatomaceous earth powder and yellow phosphorus slag powder prepared in step S1 are mixed according to the set mass ratio and added to a planetary ball mill. The ball milling process is carried out using a low-energy intermittent ball milling program. After the process is completed, the mixture is cooled to room temperature and sieved to obtain the final product.
[0045] In a preferred embodiment, in step S1, the drying can be carried out using conventional methods known to those skilled in the art, such as a drying temperature of 40~60℃; and the sieve mesh size is 100 mesh.
[0046] In a preferred embodiment, in step S2, the process parameters of the ball milling process include: the grinding balls are zirconia balls, the diameter of the grinding balls is 3~8 mm, the ball-to-material mass ratio is (5~15):1, the revolution speed is 150~300 r / min, and the total ball milling time is 50~300 min.
[0047] In a preferred embodiment, step S2, the specific operation of the low-energy intermittent ball milling program includes: milling in any single direction for 20-40 minutes, pausing for 10-20 minutes, and then milling in the opposite direction for 20-40 minutes as a cycle, and repeating the cycle 1-3 times.
[0048] In a preferred embodiment, in step S2, the sieve mesh size is 100 mesh.
[0049] A third aspect of the present invention is to provide an application of a soil conditioner for synergistic passivation of acidic cadmium and arsenic compound pollution. The soil conditioner is used for the simultaneous passivation and remediation of acidic farmland cadmium and arsenic compound pollution, and is used to simultaneously reduce the content of available cadmium and available arsenic in the soil, inhibit the migration and accumulation of cadmium and arsenic to crops, and realize the safe utilization of acidic polluted soil and simultaneous remediation and production of arable land.
[0050] In a preferred embodiment, the pH value of the acidic soil is 4.5 to 6.5.
[0051] In a preferred embodiment, the soil conditioner is applied at a rate of 1-10 g / kg.
[0052] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0053] 1. The original magnesium-iron hydrotalcite mainly relies on positively charged layers, interlayer anion exchange, and metal hydroxyl sites. This invention, through humic acid modification, introduces soft and hard coordination sites such as carboxyl and phenolic hydroxyl groups, enhancing the complexation of cations such as Cd. Furthermore, ball milling refines the particles, disrupts the layer stacking, and exposes surface hydroxyl groups, improving the accessibility of interfacial reactions. Humic acid can also influence As bonding through organic matter-Fe bridging. Simultaneously, this invention uses high-energy mechanical activation via ball milling to firmly intercalate humic acid molecules into the hydrotalcite interlayers and attach them to the surface, preventing free humic acid from forming soluble complexes with contaminants, further enhancing the cadmium-arsenic co-passivation effect. SEM comparison results show that mechanochemical modification causes the large-size, dense aggregated structure of the original magnesium-iron hydrotalcite to break down and deagglomerate, increasing particle edges, fracture surfaces, and interparticle gaps, which is beneficial for improving the accessibility of reaction sites and the dispersion of the material in the composite system.
[0054] 2. In terms of raw material design, this invention synergistically combines humic acid-modified magnesium-iron hydrotalcite, amino acid-functionalized composite hydrothermal carbon, diatomaceous earth powder, and yellow phosphorus slag powder to achieve simultaneous passivation of Cd and As through multiple reaction pathways: humic acid-modified magnesium-iron hydrotalcite primarily provides As anion exchange / Fe-OH complexation and some Cd binding sites; amino acid-functionalized composite hydrothermal carbon primarily provides nitrogen- / oxygen-containing functional groups and carbon skeletons to fix Cd and carry and disperse other components, reducing particle agglomeration and improving the mass transfer efficiency of pollutants to active sites; diatomaceous earth powder provides porous dispersion and mass transfer channels; and yellow phosphorus slag powder provides slow alkalinity and Ca-Si reaction phase in acidic soils.
[0055] 3. Regarding the dosage ratio, this invention limits the humic acid-modified magnesium-iron hydrotalcite to 30-50 parts, aiming to ensure that the humic acid-modified magnesium-iron hydrotalcite undertakes the core function of Cd-As dual-pollution co-passivation; while the amino acid functionalized composite hydrothermal carbon is limited to 20-40 parts, which can provide sufficient carbon skeleton and N / O coordination sites to avoid the risk of pollutant migration caused by excessive soluble organic matter; diatomaceous earth powder is limited to 10-30 parts, which can meet the requirements of dispersion, porosity and physical conditioning, while preventing the dilution of core active sites by an excessively high proportion of inert minerals; yellow phosphorus slag powder is limited to 5-20 parts, which is to provide sufficient buffering of acidic Ca-Si mineral phase, and can also control the risks of excessive alkalization, EC increase, phosphate competition and fluorine impurities.
[0056] 4. Regarding the preparation process, this invention employs a specific two-stage pure solid-phase ball milling method, effectively avoiding the problems of large amounts of waste liquid generated by traditional wet modification and high energy consumption caused by high-temperature calcination. In the first stage, during the preparation of humic acid-modified hydrotalcite, high-energy mechanical activation is used to intercalate and modify the original magnesium-iron hydrotalcite, enhancing its complexation capacity for Cd and As. In the second stage, low-speed intermittent ball milling is used to mechanically and chemically composite the modified hydrotalcite with solid waste raw materials such as hydrothermal carbon and yellow phosphorus slag powder. This is not only a simple mixing process but also increases the interfacial contact between different particles and shortens the mass transfer distance of pollutants. In particular, corresponding pause times are designed in both stages of the pure solid-phase ball milling process for temperature control and heat dissipation, preventing prolonged high-energy ball milling from completely destroying the layered structure of LDH and the pores of hydrothermal carbon. The overall process steps of this invention are simple and the conditions are mild, effectively controlling the operating energy consumption of the equipment and avoiding the damage to the porous structure of the material caused by prolonged high-energy ball milling of all components.
[0057] 5. In practical applications, the composite conditioner provided by this invention breaks through the bottleneck of high-dose application of traditional materials, exhibiting excellent passivation efficacy at extremely low application rates (5 g / kg), significantly reducing remediation costs and engineering difficulty. Simultaneously, this invention effectively blocks the migration and accumulation of heavy metals into crop tissues, significantly alleviating heavy metal toxicity stress in crops, reducing soil ecological risks while ensuring stable crop yields, highly meeting the practical needs of "remediation while production" in farmland with compound pollution. Furthermore, this technology successfully transforms agricultural waste and industrial solid waste into high-value-added environmentally friendly products, achieving a win-win situation of high-value utilization of multi-source waste and long-term improvement of soil ecology. Attached Figure Description
[0058] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0059] Figure 1 Scanning electron microscope images of the original magnesium-iron hydrotalcite (a) and humic acid modified magnesium-iron hydrotalcite (MH-LDHs) (b) prepared for embodiments of the present invention;
[0060] Figure 2 X-ray diffraction pattern of humic acid modified magnesium-iron hydrotalcite (MH-LDHs) prepared in the embodiments of the present invention;
[0061] Figure 3 The effects of Examples 1 and 2 and Comparative Examples 1-2 on the available Cd content in soil;
[0062] Figure 4 The effects of Examples 1 and 2 and Comparative Examples 1-2 on the content of available As in soil;
[0063] Figure 5 The effects of Examples 1 and 2 and Comparative Examples 1-2 on the Cd content in the aboveground parts of Chinese cabbage;
[0064] Figure 6 Examples and Comparative Examples 1-2 illustrate the effect of As content in the aboveground parts of Chinese cabbage;
[0065] Figure 7 The effects of Examples 1 and 2 and Comparative Examples 1-2 on the Cd content in the underground parts of Chinese cabbage;
[0066] Figure 8 Examples and Comparative Examples 1-2 illustrate the effect of As content in the underground parts of Chinese cabbage.
[0067] Figure 9 Examples and Comparative Examples 1-2 illustrate the effect of these examples on the fresh weight of the above-ground parts of Chinese cabbage.
[0068] Figure 10 The effects of Examples 1 and 2 and Comparative Examples 1-2 on the aboveground dry weight of Chinese cabbage were studied. Detailed Implementation
[0069] To enable those skilled in the art to better understand the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. However, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0070] Unless otherwise specified, the technical means used in this invention are conventional means well known to those skilled in the art. All raw materials, reagents, instruments, and equipment used in this invention can be purchased commercially or prepared using existing methods. Unless otherwise specified, all reagents used in this invention are of analytical grade.
[0071] In this embodiment of the invention, the humic acid used is a powdered product with a humic acid content of not less than 90%, and the manufacturer is Haiyuanye Biotechnology Co., Ltd., with product number S30583.
[0072] The amino acid mother liquor used was prepared by concentrating the residue left over from the production of valine. Its main components are valine and sugars, including 70g / L of free amino acids, 150g / L of organic matter, and pH 5. The manufacturer is Anhui Huaheng Biotechnology Co., Ltd.
[0073] The diatomaceous earth powder used is unmodified organic diatomaceous earth powder, manufactured by Liaoning Yimushen Agricultural Technology Co., Ltd. The chemical composition of the diatomaceous earth powder, based on the mass percentage analysis of X-ray fluorescence spectroscopy (XRF), mainly includes: CaO 35.0%~45.0%, SiO2 30.0%~40.0%, Al2O3 2.0%~6.0%, P2O5 2.0%~5.0%, MgO 1.0%~4.0%, K2O 1.0%~4.0%, with the balance being trace elements and unavoidable impurities.
[0074] The yellow phosphorus slag powder used is unmodified yellow phosphorus slag powder, manufactured by Jiangxi Haiwei Environmental Protection Technology (Group) Co., Ltd.; the chemical composition of the yellow phosphorus slag powder, based on the mass percentage analysis of X-ray fluorescence spectroscopy (XRF), mainly includes: SiO2 60.0%~75.0%, Al2O3 10.0%~18.0%, K2O 3.0%~8.0%, Na2O 2.0%~6.0%, CaO 1.0%~5.0%, Fe2O3 1.0%~4.0%, with the balance being trace elements and unavoidable impurities.
[0075] In this invention, the weight parts can be weight units known in the art such as µg, mg, g, kg, or multiples thereof, such as 1 / 10, 1 / 100, 10 times, 100 times, etc.
[0076] Example 1
[0077] A soil conditioner for synergistic passivation of acidic cadmium and arsenic compound pollution comprises, by weight: 40 parts humic acid-modified hydrotalcite (MH-LDHs), 30 parts amino acid-functionalized composite hydrothermal carbon, 20 parts diatomaceous earth powder, and 10 parts yellow phosphorus slag powder. Its preparation method specifically includes the following steps:
[0078] Step S1 involves preparing humic acid-modified hydrotalcite and amino acid-functionalized composite hydrothermal carbon, while pretreating diatomaceous earth powder and yellow phosphorus slag powder. The following steps A, B, and C are in no particular order:
[0079] (A) Preparation of humic acid-modified hydrotalcite (MH-LDHs):
[0080] (1) Dissolve 8.13 g MgCl2·6H2O and 3.24 g anhydrous FeCl3 in an appropriate amount of deionized water, and add deionized water to make up to 100 mL to obtain Mg 2+ with Fe 3+ A mixed metal salt solution with a molar ratio of 2:1 and a total metal ion concentration of 0.6 mol / L was prepared; 800 mL of an alkaline solution with a concentration of 0.15 mol / L was prepared using sodium hydroxide (i.e., the molar amount of sodium hydroxide in the alkaline solution was equal to the molar amount of Mg in the metal salt solution). 2+ with Fe 3+ (twice the total molar amount), the metal solution and the alkaline solution were simultaneously poured into a colloid mill at the same rate for a high-speed shear reaction at a speed of 4000 r / min for 3 minutes; then the reactants were transferred to a beaker and aged at 1000 r / min for 4 hours under constant temperature of 80℃; after centrifugation and washing with deionized water 5 times to completely remove impurity ions, the mixture was finally dried thoroughly in an oven at 60℃ for 6 hours and ground through a 100-mesh sieve to obtain the original magnesium-iron hydrotalcite.
[0081] (2) Raw magnesium-iron hydrotalcite and humic acid (HA, molecular weight 321 kDa, content above 90%) were added to a planetary ball mill at a mass ratio of 10:1 for high-energy mechanical activation. After the treatment, the mixture was cooled to room temperature to obtain MH-LDHs prepared by the first stage of high-energy mechanical activation. The ball milling process parameters included: the grinding balls were zirconia balls with a diameter of 5 mm, the ball-to-material mass ratio was 6:1, the revolution speed was 300 r / min, and the total ball milling time was 10 h. The specific operation of high-energy mechanical activation included: one cycle of clockwise ball milling for 1 h, pausing for 0.5 h, and counterclockwise ball milling for 1 h, and repeating the cycle 4 times. After cooling to room temperature, MH-LDHs prepared by the first stage of high-energy mechanical activation were obtained.
[0082] (B) Preparation of amino acid-functionalized composite hydrothermal carbon (HTC):
[0083] Waste cotton stalks were rinsed with deionized water to remove surface impurities, placed in a forced-air drying oven and dried at 70℃ to constant weight. The dried stalks were then pulverized and passed through a 100-mesh sieve, and the undersize was collected to obtain cotton stalk powder. Natural lignite was also pulverized and passed through a 100-mesh sieve, and the undersize was collected to obtain lignite powder. 300 g of cotton stalk powder and 300 g of lignite powder (mass ratio 1:1) were accurately weighed and mixed evenly to obtain 600 g of solid precursor. Amino acid mother liquor was diluted with deionized water at a volume ratio of 1:50, and 6 L of the diluted amino acid was added to a 10 L high-pressure reactor. The solid precursor was slowly poured into the reactor and stirred to infiltrate. The reactor was sealed, and the temperature was increased to 220℃ at 5℃ / min, and the reaction was maintained at this temperature for 2 hours. After cooling, the solid was separated by filtration, dried under vacuum at 80℃ for 12 hours, and then ground and passed through a 100-mesh sieve to obtain HTC.
[0084] (C) Pretreatment of polysilicon-phosphate precursors:
[0085] Diatomaceous earth powder and yellow phosphorus slag powder were placed in an oven and dried thoroughly to constant weight, and then passed through a 100-mesh sieve for later use.
[0086] Step S2: Low-energy intermittent ball milling compounding:
[0087] Weigh out 40 parts of MH-LDHs, 30 parts of HTC, 20 parts of diatomaceous earth powder, and 10 parts of yellow phosphorus slag powder according to the above-mentioned weight proportions. Mix them and add them to a planetary ball mill. Use a low-energy intermittent ball milling program for ball milling. After processing, cool to room temperature and pass through a 100-mesh sieve to obtain the soil conditioner. The ball milling process parameters include: the grinding balls are zirconia balls with a diameter of 5 mm, the ball-to-material mass ratio is 10:1, the revolution speed is 200 r / min, and the total ball milling time is 150 minutes. The specific operation of the low-energy intermittent ball milling program includes: ball milling in one direction for 30 minutes, pausing for 15 minutes to control the temperature and dissipate heat, and then ball milling in the opposite direction for 30 minutes. This step is considered a complete cycle and is executed twice.
[0088] This embodiment systematically characterized the MH-LDHs prepared in step (a), specifically including:
[0089] Morphological observation: Scanning electron microscope images of primitive magnesium-iron hydrotalcite and MH-LDHs are shown below. Figure 1 As shown, where Figure 1 (a) is the original magnesium-iron hydrotalcite. Figure 1 (b) refers to MH-LDHs; by Figure 1 (a) It can be seen that the original magnesium-iron hydrotalcite mainly exhibits a large, massive aggregate structure, with relatively tight stacking between the layers, resulting in a relatively dense overall particle size. Figure 1(b) As can be seen, after humic acid compounding and high-energy ball milling, the large-sized flaky particles in MH-LDHs are broken and deagglomerated, forming more irregular flaky and granular structures of smaller size. The material surface is rougher, and the edges of the flaks, fracture surfaces, and interparticle gaps are significantly increased, resulting in a relatively loose particle packing structure. These changes are beneficial for increasing the interfacial contact area between the material and the pollutants, improving the accessibility of metal hydroxyl sites and oxygen-containing functional groups of humic acid on the surface of hydrotalcite, and facilitating the uniform dispersion of MH-LDHs in subsequent compounding processes, thus providing a favorable structural basis for the simultaneous passivation of Cd and As.
[0090] Phase analysis: X-ray diffraction patterns of MH-LDHs are as follows Figure 2 As shown, MH-LDHs exhibit distinct (003), (006), and (009) crystal plane characteristic diffraction peaks around 2θ of approximately 11.21°, 22.60°, and 33.91°, with interplanar spacings of approximately 0.79 nm, 0.39 nm, and 0.26 nm, respectively. The characteristic diffraction peaks at lower angles indicate that the obtained material retains the layered structure of magnesium-iron hydrotalcite. Simultaneously, some diffraction peaks show a certain degree of broadening, suggesting that after humic acid composite treatment and high-energy ball milling, the grain size of the material may have decreased, and the regularity of the layer stacking and crystallinity may have been reduced, but the main crystal structure of hydrotalcite was not completely destroyed.
[0091] Pore structure analysis: The average pore size of MH-LDHs, measured by the BET / BJH method, was 20.9768 nm, and the pore volume was 0.038320 cm³. 3 g −1 Its specific surface area is 6.6377 m². 2 g −1 .
[0092] In this embodiment, elemental analysis (EA) was performed on the HTC prepared in step (b). The results showed that the mass fractions of C, H, N, S and O in the sample were 44.22%, 4.62%, 2.26%, 0.77% and 25.87%, respectively.
[0093] Comparative Example 1
[0094] This comparative example aims to verify the passivation effect of retaining only carbon-based and hydrotalcite after stripping the polysilicon-phosphate multi-mineral system.
[0095] The specific preparation method is as follows: Take 50 parts of humic acid-modified hydrotalcite prepared by the same method as in Example 1, and 50 parts of amino acid-functionalized composite hydrothermal carbon prepared by the same method as in Example 1, without adding diatomaceous earth powder or yellow phosphorus slag powder. Mix the two raw materials evenly and add them to a planetary ball mill. Process the materials according to the same ball milling process parameters and low-energy intermittent ball milling program as in Example 1, and the resulting material is a mineral-free composite material.
[0096] Comparative Example 2
[0097] This comparative example aims to verify the passivation effect of retaining only the multi-mineral system after stripping the carbon-based framework and hydrotalcite.
[0098] The specific preparation method is as follows: Take 50 parts of diatomaceous earth powder and 50 parts of yellow phosphorus slag powder that have been pretreated using the same method as in Example 1, without adding MH-LDHs and HTC. Mix the two raw materials evenly and add them to a planetary ball mill. Process the materials according to the same ball milling process parameters and low-energy intermittent ball milling program as in Example 1. The finished product is a carbon-free and water-free talc composite material.
[0099] Application Example 1
[0100] Indoor incubation experiment on cadmium-arsenic co-contaminated soil
[0101] In this application example, topsoil from farmland in Shaoguan City, Guangdong Province, my country, which is contaminated with Cd and As (total Cd 0.76 mg / kg, total As 28.95 mg / kg, initial pH 5.07), was used as the research object to verify the material's retention capacity in complex soil environments. Specific experimental methods included:
[0102] (1) Preparation of test soil and soil culture
[0103] The test soil was collected from the topsoil layer of Cd and As contaminated farmland in Shaoguan City, Guangdong Province. The soil was air-dried, pulverized, and sieved through a 2 mm sieve. 50 g of the test soil was accurately weighed and placed in a culture container, and the materials were thoroughly mixed with the soil at a rate of 5 g / kg. A blank control group (CK) without any additives was also set up. Deionized water was added to the containers to adjust the soil moisture content to 60% of the maximum field capacity. The culture containers were placed at room temperature and kept in the dark for 14 days, with water added periodically to maintain a constant moisture content.
[0104] (2) Determination of available soil contents
[0105] After the incubation period, the soil samples from each treatment group were air-dried naturally, and the available Cd and As in the soil were determined using the following method.
[0106] Available Cd in soil (DTPA-Cd): 14.92 g of triethanolamine, 1.967 g of diallyltriaminepentaacetic acid, and 1.470 g of calcium chloride dihydrate were weighed and added to a beaker. Water was added and stirred until completely dissolved. The solution was further diluted with water to approximately 800 mL. The pH was adjusted to 7.3 ± 0.2 with hydrochloric acid solution. The solution was then transferred to a 1 L volumetric flask and brought to a final volume to obtain the soil DTPA extract. 10.0 g of soil was weighed and 20 mL of the extract was added. The mixture was shaken for 2 h, centrifuged at 4500 r / min for 10 min, and the supernatant was filtered through a 0.22 μm filter. The Cd concentration was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0107] Soil available As (NaHCO3-As): Prepare 0.5 mol·L -1 To prepare the NaHCO3 solution, weigh 1 g of soil, add 30 mL of NaHCO3 solution, shake for 2 h, then filter through a 0.22 μm filter membrane, and determine the As concentration using an atomic fluorescence spectrophotometer.
[0108] Results and Discussion:
[0109] The effects of different treatment groups on the content of available Cd in the soil are as follows: Figure 3 As shown, the soil with the highest available Cd content in the blank control group (CK) without the application of amendment was 0.28 mg / kg; the soil with available Cd content after treatment with the material of the present invention was 0.09 mg / kg, which was significantly lower than that of Comparative Example 1 (0.12 mg / kg) which stripped the polymineral system and Comparative Example 2 (0.15 mg / kg) which only retained the polymineral system.
[0110] The effects of different treatment groups on the content of available As in the soil are as follows: Figure 4 As shown, the available As content in the soil of the blank control group (CK) was 0.96 mg / kg; the available As content in the soil of the example group was 0.46 mg / kg, which was also significantly lower than that of Comparative Example 1 (0.61 mg / kg) and Comparative Example 2 (0.65 mg / kg).
[0111] Therefore, it can be seen that the soil conditioner prepared in the embodiments of the present invention simultaneously reduces the content of available cadmium and available arsenic in acidic soil.
[0112] Application Example 2
[0113] Potted plants in acidic soil undergo co-passivation and plant growth promotion experiment
[0114] This application example, building upon Application Example 1, further verifies the long-term stabilization and plant desensitization effects of the material in a real agricultural planting environment. The same test soil and "Jingcui 60" Chinese cabbage variety as in Application Example 1 were used as the research subjects. Specific experimental methods included:
[0115] (1) Seedling raising and management of Chinese cabbage in plug trays
[0116] Cabbage seeds were raised in seed trays using substrate soil. After sowing and watering, the surface was covered with a black plastic film to provide shade, warmth, and moisture. Three days after sowing, once the cabbage seedlings emerged, the film was removed, and watering was carried out regularly before 10:00 AM daily thereafter. When the cabbage had two cotyledons, the seedlings were thinned, leaving 1-2 strong seedlings per hole, and continued to be cultivated until the "two leaves and one heart" stage (approximately 15 days) for later use.
[0117] (2) Soil preparation and transplanting of potted plants
[0118] One week before transplanting the cabbage, the test soil and passivation materials were thoroughly mixed and equilibrated according to the experimental treatment protocol. One day before transplanting, the mixed soil was divided into plastic pots with an inner diameter of 14.5 cm and a height of 14 cm, with each pot containing 1000 g of soil. The pots were watered regularly with deionized water to maintain suitable soil moisture. After the soil preparation was completed, the cabbage seedlings, which had been cultivated for 15 days, were transplanted into the pots.
[0119] (3) Harvesting and fresh weight determination of plants
[0120] The Chinese cabbage seedlings are harvested 21 days after transplanting. During harvest, the above-ground and underground parts of the cabbage are separated using scissors; loose soil around the roots is gently shaken off, and the roots are then slowly rinsed in tap water to remove any adhering soil. After rinsing, the surface moisture of the plant is thoroughly dried with absorbent paper, and the fresh weight of the above-ground and underground parts of the cabbage is immediately measured and recorded.
[0121] (4) Processing and preservation of plant and soil samples
[0122] After recording the fresh weight, the plant samples were placed in a 105℃ constant temperature drying oven for 30 minutes to kill the green color. Then, the temperature was adjusted to 75℃ and dried to constant weight. The dry weight of the plants was weighed and recorded. Finally, the dried plant samples were ground into powder, sealed and stored for testing.
[0123] (5) Determination of heavy metal (Cd, As) content in aboveground and underground parts of plants
[0124] Accurately weigh 0.2 g of the dried powder of the above-ground and underground parts of Chinese cabbage prepared in step 1.2.4 into a digestion tube, add 8 mL of HNO3, digest in a microwave digester, and determine the concentrations of Cd and As using an inductively coupled plasma optical emission spectrometer (ICP-OES).
[0125] Results and Discussion:
[0126] The effects of different treatment groups on the Cd and As content in the aboveground parts of Chinese cabbage are as follows: Figure 5 and 6 As shown. By Figure 5 It can be seen that the highest Cd content in the aboveground parts of Chinese cabbage was found in the blank control group (CK) without any amendment, at 0.46 mg / kg. The Cd content in the aboveground parts of Chinese cabbage treated with the materials of this invention was significantly reduced to 0.30 mg / kg, significantly lower than that in Comparative Example 1 (0.41 mg / kg) lacking the silicon-phosphorus polymineralic system and Comparative Example 2 (0.43 mg / kg) lacking the carbon-based and hydrotalcite framework. Figure 6 It can be seen that the As content in the aboveground parts of cabbage in the blank control group (CK) was 2.93 mg / kg; the As content in the aboveground parts of the example group after treatment was reduced to 2.54 mg / kg, which was also lower than that in comparative example 1 (2.63 mg / kg) and comparative example 2 (2.72 mg / kg).
[0127] The effects of different treatment groups on the Cd and As content in the underground parts of Chinese cabbage are as follows: Figure 7 and 8 As shown. By Figure 7 It was found that the Cd content in the underground parts of the cabbage in the blank control group (CK) was 0.42 mg / kg; the Cd content in the underground parts of the treated example group was 0.35 mg / kg, which was lower than that in Comparative Example 1 (0.39 mg / kg) and Comparative Example 2 (0.38 mg / kg). Figure 8 It can be seen that the As content in the underground part of Chinese cabbage in the blank control group (CK) was the highest, at 14.83 mg / kg; the As content in the underground part of the example group after treatment was significantly reduced to 11.02 mg / kg, and the overall passivation effect was better than that of comparative example 1 (11.56 mg / kg) and comparative example 2 (12.47 mg / kg).
[0128] The effects of different treatment groups on the fresh weight and dry weight of the aboveground parts of Chinese cabbage are as follows: Figure 9 and 10 As shown.
[0129] Depend on Figure 9It can be seen that the blank control group (CK) without the treatment agent was affected by heavy metal toxicity stress, resulting in a low aboveground fresh weight of 62.45 g / plant. However, after treatment with the material of the present invention, the aboveground fresh weight of the cabbage significantly increased to 72.04 g / plant, which was significantly better than Comparative Example 1 (70.53 g / plant) lacking the multi-mineral system and Comparative Example 2 (66.47 g / plant) retaining only the multi-mineral system. After treatment with the material of the present invention, the aboveground fresh weight of the cabbage increased by 15.4% (compared to the CK group), 2.1% (compared to Comparative Example 1), and 8.4% (compared to Comparative Example 2), respectively.
[0130] Depend on Figure 10 It can be seen that the effects of each treatment group on the aboveground dry weight of Chinese cabbage are basically consistent with the effects on fresh weight. The aboveground dry weight of the blank control group (CK) was 5.03 g / plant; the aboveground dry weight of the treatment group was the highest, increasing to 5.63 g / plant, which was also higher than that of Comparative Example 1 (5.51 g / plant). It is worth noting that the dry weight of Comparative Example 2 (4.93 g / plant) was even slightly lower than that of the blank control group, indicating that the single multi-mineral system failed to effectively promote dry matter accumulation under these conditions.
[0131] In summary, the comparative data from indoor soil cultivation and pot experiments show that the composite amendment provided by this invention exhibits a significant synergistic inhibitory effect on cadmium and arsenic in acidic soils. Compared to formulations lacking the multi-mineral system (Comparative Example 1) or the carbon-based and hydrotalcite framework (Comparative Example 2), the complete composite system, applied at a low dose of only 5 g / kg, can significantly reduce the content of available Cd and As in the soil. At the plant level, the amendment of this invention effectively inhibits the migration of heavy metals to the roots and aboveground parts of cabbage, significantly reduces the accumulation of cadmium and arsenic in plant tissues, substantially alleviates heavy metal toxicity stress, and directly manifests as a significant increase in the fresh and dry weight of the aboveground parts of the crop. The above experimental results confirm that the humic acid-modified hydrotalcite, amino acid-based hydrothermal carbon, and silicon-phosphorus multi-mineral system, after being compounded, form an effective synergistic mechanism that can significantly reduce the bioavailability of heavy metals in acidic composite polluted soils, providing reliable data for quantitative application in real-world environments.
[0132] The foregoing description of specific exemplary embodiments of the invention is for illustrative and explanatory purposes. These descriptions are not intended to limit the invention to the precise forms disclosed, and it will be apparent that many changes and variations can be made in accordance with the foregoing teachings. The exemplary embodiments were chosen and described in order to explain the specific principles of the invention and its practical application, thereby enabling those skilled in the art to implement and utilize various different exemplary embodiments of the invention, as well as various different choices and variations. The scope of the invention is intended to be defined by the claims and their equivalents.
Claims
1. A soil conditioner for synergistic passivation of acidic cadmium and arsenic compound pollution, characterized in that, By weight, it includes the following components: 30-50 parts of humic acid modified hydrotalcite, 20-40 parts of amino acid functionalized composite hydrothermal carbon, 10-30 parts of diatomite powder, and 5-20 parts of yellow phosphorus slag powder.
2. The acidic cadmium-arsenic composite pollution synergistic passivation soil conditioner as described in claim 1, characterized in that, The preparation method of the humic acid modified hydrotalcite includes the following steps: (1) Dissolve soluble magnesium salt and soluble iron salt in deionized water to prepare a mixed metal salt solution, then mix it with alkaline solution, react it by nucleation crystallization isolation method, and age it by constant temperature stirring to obtain the original magnesium iron hydrotalcite powder. (2) Mix the original magnesium-iron hydrotalcite powder with humic acid. The resulting mixture is then subjected to high-energy mechanical activation by ball milling, which allows humic acid molecules to be firmly intercalated into the hydrotalcite interlayer and attached to the surface, resulting in humic acid-modified hydrotalcite, denoted as MH-LDHs.
3. The acidic cadmium-arsenic compound pollution synergistic passivation soil conditioner as described in claim 2, characterized in that, In step (1), in the mixed metal salt solution, Mg 2+ with Fe 3+ The molar ratio is (1~3):1, and the total metal ion concentration is 0.1~0.6 mol / L; The alkaline solution is an aqueous solution of sodium hydroxide, and the concentration of sodium hydroxide in the alkaline solution is 0.1~0.2 mol / L. The molar amount of sodium hydroxide in the alkaline solution is equal to the molar amount of Mg in the mixed metal salt solution. 2+ with Fe 3+ 1.8 to 2.5 times the total molar amount; The constant temperature is 75~85℃, and the stirring and aging time is 3~5 h.
4. The acidic cadmium-arsenic compound pollution synergistic passivation soil conditioner as described in claim 2, characterized in that, In step (2), the mass ratio of the original magnesium-iron hydrotalcite powder to humic acid is (8~12):1; The specific operation of the high-energy mechanical activation includes: performing a cycle of clockwise ball milling for 1 hour, pausing for 0.5 hours, and counterclockwise ball milling for 1 hour, and repeating this cycle 3 to 5 times.
5. The acidic cadmium-arsenic compound pollution synergistic passivation soil conditioner as described in claim 1, characterized in that, The preparation method of the amino acid functionalized composite hydrothermal carbon includes the following steps: cotton straw powder and lignite powder are mixed as solid precursors, diluted amino acid mother liquor is added, and the mixture is heated to 200~240°C and kept at a constant temperature in a closed reaction vessel to carry out a co-hydrothermal reaction to obtain amino acid functionalized composite hydrothermal carbon, denoted as HTC.
6. The soil conditioner for synergistic passivation of acidic cadmium and arsenic compound pollution as described in claim 5, characterized in that, The mass ratio of cotton stalk powder to lignite powder is 1:(0.8~1.2); the diluted amino acid mother liquor is obtained by diluting amino acid mother liquor with deionized water at a volume ratio of 1:(30~70), and the main components of the amino acid mother liquor include 50~90 g / L of free amino acids, 100~200 g / L of organic matter, and a pH of 4~6; the solid-liquid ratio of the solid precursor to the diluted amino acid mother liquor is 1g:(8~12)mL; the co-hydrothermal reaction time is 1~3 h.
7. The preparation method of the acidic cadmium-arsenic composite pollution synergistic passivation soil conditioner as described in any one of claims 1-6, characterized in that, Includes the following steps: S1 prepared humic acid-modified hydrotalcite and amino acid-functionalized composite hydrothermal carbon for later use; diatomaceous earth powder and yellow phosphorus slag powder were dried to constant weight and sieved for later use. S2. The humic acid-modified hydrotalcite, amino acid-functionalized composite hydrothermal carbon, diatomaceous earth powder and yellow phosphorus slag powder prepared in step S1 are mixed according to the set mass ratio and added to a planetary ball mill. The ball milling process is carried out using a low-energy intermittent ball milling program. After the process is completed, the mixture is cooled to room temperature and sieved to obtain the final product.
8. The preparation method of the acidic cadmium-arsenic composite pollution synergistic passivation soil conditioner as described in claim 7, characterized in that, In step S1, the sieve mesh size is 100 mesh; In step S2, the specific operation of the low-energy intermittent ball milling program includes: milling in any single direction for 20-40 minutes, pausing for 10-20 minutes, and then milling in the opposite direction for 20-40 minutes as a cycle, and repeating the cycle 1-3 times.
9. The application of the acidic cadmium-arsenic compound pollution synergistic passivation soil conditioner as described in any one of claims 1-6, characterized in that, The soil conditioner is used for the simultaneous passivation and remediation of cadmium and arsenic compound pollution in acidic farmland. It is used to simultaneously reduce the content of available cadmium and arsenic in the soil, inhibit the migration and accumulation of cadmium and arsenic to crops, and realize the safe utilization of acidic polluted soil and simultaneous remediation and production of arable land.
10. The application of the acidic cadmium-arsenic compound pollution synergistic passivation soil conditioner as described in claim 9, characterized in that, The pH value of the acidic soil is 4.5~6.5; the application rate of the soil conditioner is 1~10 g / kg.